COVID-19, THE PANDEMIC THAT MAY SAVE THE WORLD FROM WAR AND CHANGE IT TO A BETTER PLACE FOR THE LIVING - Rasheed Adeniyi Tiamiyu; Junior Hendri Wijaya (CV The Journal Publishing, 2020)
Allegations and counter-allegations surrounding the advent of the novel coronavirus (COVID-19) are heavily skewed toward the commencement of the biological war, even though it has been observed over the years that war has a tremendous negative effect on all facets of human endeavor, for which the United Nations has applied series of sanctions to enforce its decisions to prevent or stop the existing war. For instance, powerful world leaders hand twist decisions of the United Nations in favor of their agenda because they see war as a means of their financial well-being. To find a solution to this issue, this paper investigated the efforts made to overcome COVID-19 and what could bring a harmonious relationship in the world. We discovered that human race is of the same origin and age-long intermarriages have further strengthened interconnectivity of the human being, such that, the blood of the citizens of a nation is running in the veins of the citizens of other nations and virus affecting whites also affects blacks and are both in need of each other to overcome the pandemic. Therefore, a program of orientation is put in place by the United Nations to orient heads of countries to imbibe and adopt absolute peaceful coexistence to prevent war in the world since one nation defending its citizens against another nation through war means to war against self.